Fogshop: Real-Time Design and Rendering of Inhomogeneous, Single-Scattering Media - Zhou, Kun; Hou, Qiming; Gong, Minmin; Snyder, John; Guo, Baining; Shum, Harry (2007)
We describe a new, analytic approximation to the airlight integral from scattering media whose density is modeled as a sum of Gaussians. The approximation supports real-time rendering of inhomogeneous media including their shadowing and scattering effects. For each Gaussian, this approximation samples the scattering integrand at the projection of its center along the view ray but models attenuation and shadowing with respect to the other Gaussians by integrating density along the fixed path from light source to 3D center to view point. Our approach handles isotropic, single-scattering media illuminated by point light sources or low-frequency environmental lighting. We also generalize models for reflectance of surfaces from constant-density to inhomogeneous media, using simple optical depth averaging in the direction of the light source or all around the receiver point. Our real-time rendering approach is incorporated into a system for real-time design and preview of realistic, animated fog, steam, or smoke. https://youtu.be/x-m5OdoGcIA